PENGARUH CONTENT MARKETING, LIVE STREAMING TIKTOK DAN PRODUCT DIVERSIFICATION TERHADAP CUSTOMER LOYALTY MELALUI BRAND AWARENESS DAN PURCHASE DECISION PADA BUTIK DIVA COLLECTION SUKOREJO - Vina Syahadatina Rhamadani; Randika Fandiyanto; Lusiana Tulhusnah (Fakultas Ekonomi dan Bisnis, 2026)
The development of digital technology and the increasing use of social media hae driven a shift in marketing strategies form convetional to more interactive digital marketing. The use of content marketing, TikTok live streaming, and Product diversification have become important strategies in building relationships with consumers, by increasing brand awareness, thereby encouraging purchase decisions, which will ultimately create customer loyalty at the Diva Collection Sukorejo Boutique. The purpose of this study is to analyze the influence of content marketing, TikTok live streaming, and Product diversification on customer loyalty through Brand awareness dan purchase decisions, This study uses a quantitative approach with an associative research type. The research population is all consumers of the Diva Collection Sukorejo Boutique. The research sample uses Hair Theory with a total of 145 respondents who are boutique consumers and have made purchase more than one. Data were collected through questionnaires analyzed using Smart PLS. 3.0. the results of the study show that content marketing, TikTok live streaming, and Product diversification have a positive but insignificant effect on brand awareness. Content marketing, and TikTok live streaming have a positive but insignificant effect on purchase decisions, while Product diversification has a positif and significant effect on purchase decisions. In addition, Brand awareness has a positive and significant effect on purchase decisions, and purchase decisions also have a positive and significant effect on customer loyalty. However, Brand awareness is unable to mediate the influence of independent variables on purchase decisions, and Brand awareness and purchase decisions are also unable to mediate their influence on customer loyalty. These findings have implivation for Butik Diva Collection Sukorejo to futher optimize digital marketing strategies and product management to increase purchase decisions and customer loyalty.